Viable bacterial counts of the Pangasius catfish (Pangasianodon hypophthalmus), their responses to seasonal variations of physicochemical parameters, and bacterial counts of the cultured ponds (Journal of Advanced Veterinary and Animal Research, 2022)
Objectives: The study was undertaken to evaluate the influences of some physicochemical parameters and viable bacterial counts in cultured ponds (water and sediment) on the viable counts of the Pangasius catfish (Pangasianodon hypophthalmus) (gill and intestine) on a seasonal scale. Materials and Methods: Physicochemical parameters, viz., ambient temperature, water temperature, water transparency, pH of the pond waters, and viable bacterial counts of pond water, sediment, fish gills, and intestines, were monitored during four different seasons. The responses of viable counts of bacteria to the seasonal changes of physicochemical parameters were also assessed using redundancy analysis (RDA) and a heatmap coupled with the clustering analysis. Results: Except for fluctuations in air and water temperatures, the other two physicochemical parameters were almost stable throughout the study periods. The gills and water counts were relatively lower than those of the intestine and sediment. Pearson’s correlation analysis established no significant correlations between the physicochemical parameters and viable bacterial counts. However, significant positive correlations were detected between the viable counts of water and sediment and between the gill and intestine. The RDA plot showed that, except in spring, the viable counts of a particular sample type were similar among the four locations. The results of permutation test showed that, individually none of the studied physicochemical parameters was significant; however, the seasons significantly affected the viable counts.J. Adv. Vet. Anim. Res., 9(4): 702–711, December 2022http://doi.org/10.5455/javar.2022.i639